Nature and Spirit in Hegel’s Anthropology: Some Idealist Themes in Hegel’s Pragmatism - Macdonald, Iain (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2007)
AbstractSome recent readings of Hegel have stressed the social dimension of Hegel’s philosophy in order to ward off common exaggerations and misconceptions about his idealism. Robert Brandom, for example, has pointed to “pragmatist themes in Hegel’s idealism.” But a general question arises as to whether this deflationary strategy really does justice to Hegel’s thought : what becomes of the logical preconditions for knowledge and agency, on which Hegel places much emphasis, and how exactly do these preconditions mesh with the natural and social dimensions of experience ? On the basis of passages in the Encyclopedia and other texts, this paper argues for a modest transcendentalism in Hegel, in order to avoid the over-correction that consists in reducing Hegel’s concept of the concept to a network of social practices.